Ground-penetrating radar and electrical resistivity tomography surveys at the Cerrate Abbey (Lecce, Italy). Issue 5 (3rd September 2022) - Leucci, Giovanni; De Giorgi, Lara; Ditaranto, Immacolata; Miccoli, Ilaria; Scardozzi, Giuseppe
Abstract : The results of the geophysical surveys carried out in 2019 in the Abbey of Santa Maria di Cerrate (Lecce) are presented in this paper. The objective of this study was to achieve a better knowledge of the site, since it was only partially investigated by small archaeological excavation samples. The geophysical measurements were conducted inside and outside the church in order to identify buried ancient structures, using both the georadar and geoelectrical survey methodologies. The results of GPR (ground-penetrating radar), ERT (electrical resistivity tomography) and IP (induced polarisation) were jointly analysed with archaeological data already known and were georeferenced on the general plans of the site in order to obtain an overall view of the anomalies detected by geophysical instrumentation and probably linked to buried ancient structures.